2007
DOI: 10.4114/ia.v11i36.890
|View full text |Cite
|
Sign up to set email alerts
|

Extract-biased pseudo-revelance feedback

Abstract: Successfully retrieving a web document is a twofold problem: having an adequate query that can usefully and properly help filtering relevant documents from huge collections, and presenting the user those that may indeed fulfill his/her needs. In this paper, we focus on the first issue -the problem of having a misleading user query. The aim of the work is to refine a query by using extracts instead of full documents. Extracts, in our context, are actually summaries of documents of a hitlist produced by an extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Summaries are also important tools for other automatic tasks. In information retrieval, for instance, it was shown that indexing summaries may be better than indexing the complete documents (see, e.g., [10]) and that summaries are useful for refining queries (e.g., [1]).…”
Section: Introductionmentioning
confidence: 99%
“…Summaries are also important tools for other automatic tasks. In information retrieval, for instance, it was shown that indexing summaries may be better than indexing the complete documents (see, e.g., [10]) and that summaries are useful for refining queries (e.g., [1]).…”
Section: Introductionmentioning
confidence: 99%